Pengaruh Aplikasi Larutan Daun Sirih Hijau (Piper betle L.) Terhadap Intensitas Serangan Hama Daun Pada Tanaman Sawi Pakcoy (Brassica rapa L.) - Rejeki, Endang Dwi; Rizali, Akhmad; Gazali, Akhmad (Agroekotek View, 2025)
Pakchoy mustard greens, also known as Brassica rapa L., is a very popular vegetable and belongs to the mustard greens family or known as Brassicaceae. This vegetable is very popular and loved by Indonesian people. Pakchoy mustard greens are widely planted by farmers in Indonesia because they have high economic value and nutritional content. There are several factors that can hinder the decline in the quality and quantity of the pakchoy mustard crop harvest, one of which is disturbance caused by pests. The aim of this research was to determine the effect of administering green betel leaf solution and to determine the most effective concentration of green betel leaf solution in reducing the intensity of pest attacks on Pakchoy mustard plants. This research used a one-factor Randomized Block Design (RAK). The factors studied were the treatment of green betel leaf solution (P) with five concentration levels which were repeated in 4 repetitions so that 20 experimental units were obtained. P0: Control (0% concentration); P1: Concentration 65% (65 ml green betel leaf solution + 35 ml water); P2: Concentration 70% (70 ml green betel leaf solution + 30 ml water); P3: Concentration 75% (75 ml green betel leaf solution + 25 ml water); P4: Concentration 80% (80 ml of green betel leaf solution + 20 ml of water). The results of the research showed that the administration of green betel leaf solutions with various concentrations had a significant effect on the intensity of pest attacks on pakchoy mustard plants. The treatment of giving 80 ml of green betel leaf solution + 20 ml of water is the best concentration that can reduce the level of pest attacks on Pakchoy mustard greens, with a total percentage of pest attack intensity (31.25%).